Percepção do consumidor quanto a redução do teor de sódio em queijo de coalho por uso de microsal - Silva, Fabíola Diniz da (2017)
Cheeses are rather used for direct consumption on consumers table as in the preparation of gastronomy dishes. Salt is an importante ingredient in cheeses production due to various functions it performs. However, the amount of salt present in food has been the main focus of government agencies and consequently of food industries, since salt consumption is well above average than is indicated by the Health Ministry. One possibility is reducing sodium chloride in cheeses by a decrease in the size of salt particles (microsal), since small particle size of salt gives large sensory perception. A research looking for products and services of credit through the association of words as well as characterize the cheese of coalition with the following concentrations of sodium chloride (salt and microsal), in which, Q 1 - curd cheese with 4% of salt; Q 2 - curd cheese with 4.5% microsal; Q 3 - curd cheese with 4% microsal; Q 4 - curd cheese with 3.5% microsal. The results obtained in this research indicated that cheese is a healthy product, mainly for nutritional value, being a consumed dairy product in most cases, and consumers consider hygiene without processing a factor of great importance, being the term that defines is flavor. Consumers are looking for healthy products in their diet and cheese with reduced sodium and fat are good choices, the attributes are accepted by consumers when buying curd cheese are appearance, nutritional value and flavor. A concentration of sodium chloride that presents better results in sensorial analysis for cheese 3.5% of microsal (Q 4), obtaining a greater buy intention and make salty closer to the ideal one. The judges have identified that microsal provide a greater perception of salty taste when compared to common salt. In this way, the use of microsal as a substitute for salt in the production of curd cheese, it becomes a viable alternative. Keywords: Salt substitutes. Particle reduction. Healthy food.